The German car industry in times of decarbonisation - Carlo Jaeger; Jonas Teitge; Jan-Erik Thie; Antje Trauboth (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2023)
Long after the debates about tertiarisation and post-industrial society, deindustrialisation is a hot topic again. An important example is the future of the German car industry. Some people believe that the forces of climate policy and digitalisation will lead to a smooth shift from selling internal combustion cars to battery electric ones. We show that things are much more difficult by distinguishing three different futures. First, a pink scenario of global industrial expansion based on electric cars and renewable electricity, then, a black scenario of a shrinking market for German cars and a global car fleet far from reaching climate neutrality by 2050, finally a green scenario where carbon neutral self-driving robotaxis and shuttles on demand help realise the goals of the Paris accord and where the German car industry embraces digitalisation to sell mobility as a service, bridging the divide between private and public transport. Moreover, the pattern of incremental innovations the German innovation system is locked in is a problem. Germany needs to renew the creative capacity it had when the invention of the automobile planted the seed of the German car industry. This will require patient research able to analyse and foster an unprecedented economic transition. We explain and propose the multisectoral approach to economic dynamics developed at the interface of mathematics and economics by John von Neumann because it offers an adequate starting point for this indispensable effort.
Keywords: 330; German car industry; climate policy; climate neutrality; electric cars; Kfz-Industrie; Neue Industrialisierung; Szenariotechnik; Deutschland; Welt